Russkij naučnyj tekst "pod zontikom" kognitivnoj stilistiki - Kotûrova, Mariâ P. (Stylistyka, 2019)
The article is focused on synergetic, discursive and linguistic approaches to the Russian scientific texts. Expansion and contraction of scientific knowledge, acceleration of the process of cognition, intlation of empirical knowledge are regarded as trends of the scientifíc-cognitive activity. The author claims that “conveyer” and “flickering” cognition of scientists influences these trends and causes different faults of speech.